The Effect Of Chatbot Use On Purchase Decisions On E-Commerce Platforms With Consumer Trust As A Mediation Variable(Case Study of Consumer Behavior in Ponorogo Regency) - Suad Fikriawan; Teguh Ansori (MONETARIUM: Journal of Economics Business and Management, 2025)
This study aims to analyze the influence of chatbot usage on consumer purchasing decisions on e-commerce platforms, with trust as a mediating variable. Using a quantitative approach and a case study in Ponorogo Regency, data were collected through a closed-ended questionnaire from 30 randomly selected respondents. The research instrument was tested for validity and reliability using Pearson correlation and Cronbach's Alpha, and analyzed using simple linear regression and the Sobel mediation test. The results of the study showed that chatbots had a positive and significant effect on user trust (β = 0.68; p < 0.01), and trust significantly influenced purchasing decisions (β = 0.30; p < 0.05). The mediation test showed that trust significantly mediated the relationship between chatbots and purchasing decisions (z = 2.17; p < 0.05). These results support the Stimulus–Organism–Response (S-O-R) theoretical framework, where chatbots as stimuli influence internal conditions (trust), which then drive responses in the form of purchasing decisions. These findings emphasize the importance of chatbot design that is not only technically functional, but also capable of building user trust as a psychological relationship-based digital marketing strategy.